Evaluasi Output Arus dan Tegangan Piezoelektrik pada Media Pijakan dengan Memanfaatkaan Energi Mekanik - alvin alvin; Peprizal (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2026)
The growing demand for sustainable alternative energy sources has encouraged the development of piezoelectric-based energy harvesting systems capable of converting mechanical energy into electrical energy. This study aims to design and evaluate a piezoelectric energy harvesting prototype integrated into floor surfaces in high-foot-traffic public areas. The research methodology includes literature review, system requirement analysis, prototype design, component characterization, laboratory testing, and field evaluation. Characterization was conducted on various piezoelectric configurations (series, parallel, and combined) using different capacitors and resistive loads to determine the optimal output. The experimental results show that the combined two-module configuration produces an average voltage of up to 21.6 V and a current of 1.02 mA using a 1 µF capacitor. In human-pressure testing, the system reached a maximum of 28.7 V and 3.2 mA under an 82 kg load. The system demonstrates stable electrical output and is feasible for application in high-activity public environments. This study confirms that piezoelectric technology has significant potential as a micro-scale renewable energy solution for low-power lighting and sensor applications.